Risk Factors for Cerebral Venous Sinus Thrombosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The various clinical and neuroradiological presentations, frequency of associated prothrombotic risk factors, and predictors of outcome were studied in 42 consecutive children (ages 3 weeks to 13 years) with cerebral venous sinus thrombosis (CVST) seen at 5 European pediatric neurology centers and from stroke registries.